How does the Leader's Centrality affect Team Performance Assessment? Testing the Role of Leader's Satisfaction - Alves, Marta Pereira (2020)
The study aims to test how the association between leader's centrality (outdegree and betweenness) in the group network, considering both workflow and friendship ties between leader and members, and the perception of team performance is mediated by the leader's satisfaction with the team. The research included a total of 74 formal leaders of organizational teams from several organizations. Total, direct and indirect effects were calculated through the estimation of an OLS regression-based mediation model, controlling for team size. Results revealed that only leader's outdegree and betweenness centrality in the team friendship network positively predicted the leader's perception of team performance. In contrast to the predictions, a significant negative indirect effect of outdegree centrality of the leader within the team workflow network on the evaluation of group performance through leader's satisfaction was observed. Also, both leader´s outdegree and betweenness centrality levels in the friendship network were shown to have a positive effect on leader's assessment of team performance through leader's satisfaction with the team. Overall, findings point to the negative effects of leader's centrality in the workflow team network and the positive effects of leader's centrality in the friendship team network on his/her attitudes toward the team. The effects of the more or less central position of the leader within each of the group networks are discussed.